2021
DOI: 10.3390/plants10091835
|View full text |Cite
|
Sign up to set email alerts
|

Pilot Study: Does Contamination with Enniatin B and Beauvericin Affect the Antioxidant Capacity of Cereals Commonly Used in Animal Feeding?

Abstract: Increasing consumption of cereals has been associated with reduced risk of several chronic diseases, as they contain phytochemicals that combat oxidative stress. Cereal contamination by the “emerging mycotoxins” beauvericin (BEA) and enniatins (ENs) is a worldwide health problem that has not yet received adequate scientific attention. Their presence in feeds represents a risk for animals and a potential risk for humans because of their carry-over to animal-derived products. This preliminary study aimed to inve… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 46 publications
0
3
0
Order By: Relevance
“…Conversely, they acted antagonistically relative to cell death, which was significantly induced by ENB and counteracted by DON [65]. Furthermore, a pilot study reports that treatments with ENB reduced the antioxidant capacity in wheat, confirming the role of this mycotoxin in the induction of oxidative stress [79].…”
Section: Host Plantsmentioning
confidence: 88%
“…Conversely, they acted antagonistically relative to cell death, which was significantly induced by ENB and counteracted by DON [65]. Furthermore, a pilot study reports that treatments with ENB reduced the antioxidant capacity in wheat, confirming the role of this mycotoxin in the induction of oxidative stress [79].…”
Section: Host Plantsmentioning
confidence: 88%
“…ENN and BEA possess amphiphilic properties, as they have both hydrophilic and hydrophobic regions. This characteristic influences their interactions with biological membranes and contributes to their bioactivities, including antimicrobial, antifungal, antiviral, anticancer, insecticidal, and ionophoric activities. , However, ENN and BEA are also common contaminants of food and feed. …”
Section: Introductionmentioning
confidence: 99%
“…Early experiments in plants described an inhibition of germination and induction of wilting [ 68 , 69 ]. Recent studies have demonstrated the induction of cell death, oxidative stress, as well as the reduction of shoot length in response to ENB [ 37 , 70 ]. The role of ENNs in F. avenaceum virulence was preliminarily hypothesized [ 71 ] and subsequently confirmed in potato tubers [ 72 ].…”
Section: Introductionmentioning
confidence: 99%